Being a family caregiver for a person with Alzheimer's Disease: Unequal care (Research, Society and Development, 2025)
Alzheimer’s Disease (AD) is a neurodegenerative condition that affects memory, cognition, and autonomy, requiring continuous care. In most cases, this care is provided by women who are part of the patient’s family. This dynamic reveals the negative sociocultural impacts associated with caregiving. This study aims to understand the repercussions and feelings experienced by female caregivers participating in a Mutual Help Group (GAM). It is a qualitative research study that uses Bardin's content analysis method. Additionally, data categorization was conducted using the software Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires (IRAMUTEQ), employing classical lexicographic analysis tools and Descending Hierarchical Classification (DHC). Five thematic classes were identified and organized into three subgroups: repercussions of caregiving, strengths, and vulnerabilities. The results show that, although there are forms of support that help address the challenges, vulnerabilities still weigh more heavily on the caregivers' experiences. This suggests that the imbalance is linked to social gender constructs that place the responsibility for caregiving almost exclusively on women, which affects their physical and mental health. Thus, the study reinforces the importance of considering gender in caregiving discussions and of proposing public policies that recognize these contexts and support the caregiving role.